DENTAL IDENTIFICATION APPLICATION FOR CHILDREN USING MACROMEDIA FLASH MX 2004 - Encu Abadi; Dewi Melani Lusita., SKom., MMSI (Jurnal Sistem Informasi, 2005)
To obtain information fast and very broad in scope is not so difficult. Thedevelopment of information media is increasingly sophisticated and interesting tosolve various problems of these things. With this application is expected to becomeknowledge for children to increase knowledge about teeth and is also early learningmegenal computer technology growing today. Language described in this paper ismaking an application as a medium of information, which is shown on importantchildren's health, especially dental.